2019
DOI: 10.3389/fbioe.2019.00111
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Investigation of Disturbed Hemodynamics-Induced Tissue Degeneration in Abdominal Aortic Aneurysms Using Computational and Experimental Techniques

Abstract: Abdominal aortic aneurysm (AAA) is the dilatation of the aorta beyond 50% of the normal vessel diameter. It is reported that 4–8% of men and 0.5–1% of women above 50 years of age bear an AAA and it accounts for ~15,000 deaths per year in the United States alone. If left untreated, AAA might gradually expand until rupture; the most catastrophic complication of the aneurysmal disease that is accompanied by a striking overall mortality of 80%. The precise mechanisms leading to AAA rupture remains unclear. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 174 publications
(332 reference statements)
0
58
0
Order By: Relevance
“…The second limitation is that the G&R code does not take other factors into account, such as hemodynamics, thrombus and surrounding tissues [46][47][48][49][50][51], which may also contribute to the patient-specific AAA expansion. For example, Zambrano et al [50] has illustrated that there exist mutual effects among hemodynamics forces, intraluminal thrombus and the expansion rate of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is that the G&R code does not take other factors into account, such as hemodynamics, thrombus and surrounding tissues [46][47][48][49][50][51], which may also contribute to the patient-specific AAA expansion. For example, Zambrano et al [50] has illustrated that there exist mutual effects among hemodynamics forces, intraluminal thrombus and the expansion rate of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our research revealed an interconnected link among the anastomotic angle, the flow disturbance, and the stenotic site; specifically, when compared to the other locations in the AVF, blood flow disturbance at the stenotic site shows the strongest correlation with the AV anastomotic angle. The reconstructed patient-specific geometrical model has become a powerful tool to investigate disturbed hemodynamics and stenosis in cardiovascular diseases ( Salman et al, 2019 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study using an in vitro model showed that AAA WSS was negatively influenced by intimal thickness (Bonert et al, 2003); the inverse correlation between WSS and wall thickness increases the risk of the rupture. Inclusion of an intraluminal thrombus, which most AAAs contain, and major neighboring branching vessels additionally produced more accurate flow simulations (Vorp, 2007;Salman et al, 2019).…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%